Phytochemical Profiling and Fingerprint Analysis of Chinese Jujube (Ziziphus jujuba Mill.) Leaves of 66 Cultivars from Xinjiang Province - Song, Lijun (Molecules, 2019)
Foliage of jujube (Ziziphus jujuba Mill.) as a byproduct of agriculture, is a traditional nutraceutical material in China. Previous studies have shown that it is a rich resource of polyphenols. However, information on its complete phenolic profile and the difference between cultivars is still limited. This study investigated and compared phytochemical profiles of leaves of 66 Chinese jujube cultivars. Forty-two compounds, including 22 flavonols, two flavanols, one flavanone, 13 derivatives of phenolic acids, three simple acids, and one unknown hexoside were identified/tentatively identified using high-performance liquid chromatography (HPLC) coupled with high-resolution mass spectrometry. Eight major flavonols were quantified by HPLC coupled with an ultraviolet (UV) detector. The contents of total flavonoids ranged from 2.6–25.1 mg/g dry weight (DW). Differences between cultivars were analyzed by hierarchical cluster analysis (HCA) and principal component analysis (PCA). This study presents a systematic study on the phenolic compounds in Chinese jujube leaves of different cultivars.